Ethnomathematical Study of Jepara Troso Ikat Weaving Motifs in Two Dimensional Geometry Mathematics - Dona Oktaviani Fevironika; Rafida Salma; Eka Zuliana (Universitas Islam Sultan Agung, 2022)
The motifs on the typical Troso Jepara ikat weaving have unique shapes and patterns and have references in their design. Besides being designed according to beauty, the motifs on the Troso ikat also have their own philosophical and mathematical values. This research was conducted with the aim of describing the mathematical ideas contained in the troso ikat motif as well as the philosophical ones contained in the culture. The method in this study uses a qualitative research method with an ethnographic approach. Data collection techniques in the study were carried out directly in the field to find information by observation, interviews, and documentation. The informant in this study was Mr. Muhammad Habib as the owner of the Troso “Aida” Ikat Weaving business in Jepara, Central Java. The instruments in this study were observation sheets, interview sheets, and field documentation. Data analysis techniques used in this study are domain analysis and taxonomic analysis. The results of this study indicate that there are mathematical ideas with nuances of two-dimensional geometry in several Jepara Troso Ikat Weaving motifs including gill motifs, re-woven motifs, baron motifs feather motifs, and lurik motifs. The geometric concept in the troso ikat motif is in the form of a flat wake concept including rectangles, rhombuses, isosceles triangles, triangles, circles, hexagons, and parallelograms